Inclusive education - an equal chance for all (Confluenţe Bibliologice, 2026)
The implementation of the programme for the development of inclusive education in the Republic of Moldova will contribute to ensuring equal opportunities and access to quality education for every child at all levels of the educational system. The article describes the presentation of Educational Inclusion exhibition – a priority of the National Education, which was displayed at the International Conference „Problems of inclusive education in the Republic of Moldova: perspectives and practical solutions", which was at the Alecu Russo State University of Balti (19-20 October).
Keywords: inclusive education; thematic exhibition